Recent progress on hydroxyapatite-based dense biomaterials for load bearing bone substitutes - Nawawi, Natasha A; Alqap, Asep Sofwan F.; Sopyan, Iis (Bentham Science, 2011)

(untitled)
Hydroxyapatite (HA) is the main mineral component of bone tissue, representing ca. 69 vol% in bone and up to 98 vol% in dental enamel. Its chemical composition close to the mineral phase of bone is the origin of its excellent biocompatibility to tissue bone. Hydroxyapatite has been applied in orthopaedics as block implants, porous, granules and coating material, either dense or porous. However, the application is restricted to non-load bearing application due to its brittleness and low toughness and flexural strength. With this, the development of bioactive dense HA is necessary as it has promising potential in application of load bearing bone implant. Few efforts have been made in developing many methods to produce dense HA. Some of the methods have been combined to prepare dense HA with improved properties. This paper will be discussing the recent progress on efforts which have been done in improving mechanical properties of hydroxyapatite-based dense type biomaterials for load bearing bone substitutes applications. Some recent patents related to dense calcium phosphate are also reviewed.